2017
DOI: 10.14419/ijm.v5i1.7603
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical aspects associated with diabetic nephropathy among type 2 diabetic males in Gaza strip

Abstract: Background: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease, and the published data on various aspects of the disease is rare in Gaza Strip. Objective: to investigate clinical and biochemical aspects associated with DN among type 2 diabetic males in Gaza Strip. Methods: The study comprised 150 type 2 diabetic males from Gaza Strip. Data were obtained from a questionnaire interview, patients' records, and biochemical analysis of blood and urine samples. Statistical analysis was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Similar results were previously reported [25,26]. The significant elevation of LDH, CK and CKMB in T2DM with CVD may be explained by their specificity to CVDs diagnostic and our founding agree with others studies that illustrated cardiac enzymes have been demonstrated to be important prognostic determinants to identify high-risk patients [23,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were previously reported [25,26]. The significant elevation of LDH, CK and CKMB in T2DM with CVD may be explained by their specificity to CVDs diagnostic and our founding agree with others studies that illustrated cardiac enzymes have been demonstrated to be important prognostic determinants to identify high-risk patients [23,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 93%
“…This result was compatible with the study that showed an association between age at onset of DM and CVD development. Based on our result, there was a positive relationship between diabetes duration and CVD complication in T2DM patients and this agrees with other study showed that duration of DM had increases the risk of CHD death independent of coexisting risk factors [21][22][23]. Furthermore, Gimeno Orna JA, et al demonstrated diabetes duration superior to 15 years significantly increased cardiovascular risk of the patients and they concluded that it could be useful to consider diabetes duration in order to stratify cardiovascular risk of type 2 diabetic patients [24].…”
Section: Discussionsupporting
confidence: 92%
“…Diabetic retinopathy was associated with the duration of diabetes ( 34 , 35 ) and other microvascular and macrovascular complications ( 36 38 ). DR as expected was related to poorer glycemic control and lipid profile as well as worsening renal function ( 38 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Afzali A et al supported the association between elevated uric acid and the increased prevalence of the chronic liver disease in a prospective study [21,[26][27][28]. One potential mechanism might be responsible for the positive association between increased uric acid and elevated ALT such as Hyperuricemia and NAFLD [29].…”
Section: Discussionmentioning
confidence: 93%